Correction: Assessing the exploitation status of Johnius belangerii in Zhanjiang Bay. - Siman Deng; Dongrong Liao; Kun Lin; Shaoliang Lyu; Ning Chen; Xuefeng Wang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0314230.].